Mary climbs in : the journeys of Bruce Springsteen's women fans - Mangione, Lorraine; Luff, Donna (Rutgers University Press, 2023)
"Bruce Springsteen has been loved and cherished by his fans for decades, from his early days playing high school gymnasiums through globally successful albums and huge stadium shows to solo performances in intimate theaters. As his long and illustrious career has evolved, the legendary devotion of his fans has remained a constant. Springsteen fans have become worthy of study in their own right, with books, memoirs, and even a movie documenting their passion and perspectives. But his fans are not monolithic, and surprisingly little attention has been paid to why so many women from across the world adore The Boss. Mary Climbs In illuminates this once overlooked but increasingly important and multi-faceted conversation about female audiences for Springsteen's music. Drawing on unique surveys of fans themselves, the study offers insight into women's experiences in their own voices. Authors Lorraine Mangione and Donna Luff explore the depth of women fans' connection to Springsteen and the profound ways it which it has shaped their lives. Reflections from fans enliven each page as readers travel through a journey through the camaraderie and joy of concerts, the sorrow and confusion of personal loss and suffering, the love and closeness of a community, and the search for meaning and for the self. Viewed through a psychological lens, women fans' relationship with Springsteen is revealed in all its complexity as never before. Mary Climbs In is an important interdisciplinary contribution to the growing field of Springsteen studies and a must read for any fan"--